ATYPICAL HEMOLYTIC-UREMIC SYNDROME IN THE INTENSIVE CARE DEPARTMENT – IS IT SOMETHING EXOTIC OR NOT? (comments on the article) - Yu. S. Polushin; i. V. Shlyk; v. A. Dobronravov (Вестник анестезиологии и реаниматологии)
.